The Relationship Between the Autonomy of Turkish EFL Teachers and Their Professional Burnout - Sıla Nalbant; Selma Deneme Gençoğlu (International Journal of Contemporary Educational Research, 2025)
The aim of this study is to analyze the correlation between teacher autonomy and teacher burnout in a Turkish context. For this study, correlational research design was used, and the data were collected via the Teacher Autonomy Scale by Pearson and Hall (1993) and the Teacher Burnout Scale by Seidman and Zager (1986-1987). 100 Turkish EFL teachers who teach at high school level in public or private institutions of the center of Edirne and its districts Uzunköprü, Havsa, İpsala and Keşan were chosen as the sample for the study. The findings displayed that the participants had a low level of teacher autonomy and a moderate level of teacher burnout. The participants had a slightly higher curriculum autonomy than general autonomy. All the subcategories of the Teacher Burnout Scale showed moderate levels of teacher burnout. The highest mean was observed in the attitudes towards students subscale and the lowest mean was observed in the career satisfaction subscale. When it comes to the correlation between teacher autonomy and teacher burnout, the findings revealed that teacher burnout was significantly, inversely and moderately correlated with teacher autonomy.